PENGARUH REWARD, PUNISHMENT DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. HONDA COKROAMINOTO SARI MOTOR DENPASAR - Utami, Ni Made Satya; Wirayuda, I Kadek Agus; Saraswati, Ni Putu Ayu Sintya (Jurnal Nusa Manajemen, 2024)
Maximizing human resources is the main focus of the company in improving employee performance. The purpose of the study is to determine the effect of reward, Punishment, and organizational culture on employee performance. Population and sample of 89 employees. Data analysis techniques using validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation test, coefficient of determination, and T-test. The results obtained reward, Punishment, and organizational culture have a positive and significant effect on the performance of employees of PT. Honda Cokroaminoto Sari Motor Denpasar. The conclusion of the study Adjust R Square of 0.775 means that the independent variables are reward, punishment, and organizational culture of 77.5 percent, and 22.5 percent is explained by other variables outside the model. Suggestions for future research add transformational leadership variables or other variables that can affect employee performance.